A troublemaker’s handbook 2: how to fight back where you work and win! (Detroit, 2005)
"This oversize manual is for workers who want to take control over their lives at work. In hundreds of first-person accounts, workers tell in their own words how they did just that. The stories run from how to ridicule a pompous boss to a years-long campaign against a multinational corporation. The workplaces represented include factory and white collar, public and private, in the U.S. and Canada. Each chapter ends with questions designed to get you thinking strategically about how to apply what you've read in your workplace."